Evaluation of Fieldwork Practice Program in Computer and Network Engineering Department at SMK Negeri 6 Padang City - Ratna Yulia; Hasan Maksum; Elfi Tasrif; Eko Indrawan (Postgraduate School, Universitas Negeri Padang, 2022)
This study aims to describe the context, input, process, product of the fieldwork practice program at SMK Negeri 6 Padang City. Fieldwork practice is a mandatory program that must be carried out by schools, especially vocational and non-school education, and must be followed by students. Fieldwork practice activities help students to apply the learning outcomes obtained at school as well as a means for students to gain real experience working in accordance with conditions in the industry. This research is evaluation research with the CIPP model. The methodology used is a combination method (Mixed Methods) with a Sequential Explanatory design. The research was conducted at SMK Negeri 6 Padang City. The subjects in this study were students who had carried out fieldwork practices, the head of the working group, and several supervisors. Data collection techniques through observation, questionnaires, and interviews. The research findings show the context component in the good category with a percentage of 83 %, the input component obtained an average percentage of 76 % in the good category, the process component obtained an average percentage of 78% in the good category and the result component obtained an average percentage of 75 % with good category. It can be concluded that the fieldwork practice program at SMK Negeri 6 Padang City is good with a percentage of 77 %, but still needs improvement in several indicators to get good results.